الضريبة على الدخل المقطوع في سورية وفق المرسوم التشريعي رقم "10" لعام 2015 - إدلبي، منى محمود (جامعة البعث, 2023)
تفرض الضرائب على أرباح المهن والحرف الصناعية والتجارية وغير التجارية في سورية وفق زمرتين وهما زمره الأرباح الحقيقية، وزمرة الدخل المقطوع. وقد طال ضريبة الدخل المقطوع عدة تعديلات، فالقانون الناظم بداية لهذه الضريبة يعود لعام 1958 تحت الرقم (112)، ثم تم تنظيمها وفق القانون رقم (24) لعام 2003، ومن ثم ادخل تعديلات بشأنها بموجب المرسوم التشريعي رقم (51) لعام 2007، وأخيرا طالها تعديلات مهمة جدا بموجب المرسوم التشريعي رقم (10) لعام 2015، فكان من الضروري استعراض آخر هذه التعديلات ولا سيما أنها في غاية الأهمية، كتشكيل لجنة الإشراف، وأسس جديدة أيضا للتصنيف تختلف باختلاف المكلفين، مسلطين الضوء على الإيجابيات وأيضا السلبيات في محاولة للوصول لصياغة تشريعية جيدة بخصوص هذه الضريبة، ولا سيما أنها تطال شريحة كبيرة من المكلفين. The taxes on the profits of industrial, commercial and noncommercial occupations and trades in Syria are levied according to two groups, namely the real profits group and the group of the lumped income. The Income Tax Law has been amended several times. The law governing this tax dates back to 1958 under No. 112 and was regulated in accordance with Law No. (24) of 2003, and then amendments were made under Legislative Decree No. 51 of 2007 and finally The amendments were very important under Legislative Decree No. (10) of 2015. It was necessary to review the latest amendments, especially as there are important amendments such as the formation of a new committee on them and new foundations for classification, highlighting the pros and cons as well as the negatives in an attempt to reach legislative drafting Good regarding this tax, especially as they lug a lot of the financiers.
Keywords: ضريبة الدخل -- الربح المقطوع -- المهن العلمية -- المحاسبة الضريبية